2020
DOI: 10.1080/02701367.2020.1817295
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Parent and Child Physical Activity Using Novel Acceleration Metrics

Abstract: Purpose: This study builds a stochastic model of a discrete-time Markov chain (DTMC) that fits well with a dataset of professional playing records. Methods: The point-by-point dataset of Men's single matches played in the Association of Tennis Professionals (ATP) tour from 2011 to 2015 is analyzed. A long-debated assumption on the iid-ness in the point winning probability of the server is statistically tested. A DTMC model is then developed to analyze the dataset further. Results: The statistical test results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
5
0
1
Order By: Relevance
“…In those which did report, 51.3% of the children were girls and 68.1% of the parents were mothers. To report PA levels of children, several measuring instruments were used: questionnaires in 17 studies (unique instrument in 15 [ 25 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and together with a pedometer in two [ 55 , 56 ]), accelerometer in 11 studies [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], and pedometer in six studies (unique instrument in four [ 68 , 69 , 70 ], together with questionnaire in another two [ 55 , 56 ]). To report PA levels of parents, several measuring instruments were also used: questionnaire or survey in 24 studies (unique instrument in 23 [ 25 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In those which did report, 51.3% of the children were girls and 68.1% of the parents were mothers. To report PA levels of children, several measuring instruments were used: questionnaires in 17 studies (unique instrument in 15 [ 25 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and together with a pedometer in two [ 55 , 56 ]), accelerometer in 11 studies [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], and pedometer in six studies (unique instrument in four [ 68 , 69 , 70 ], together with questionnaire in another two [ 55 , 56 ]). To report PA levels of parents, several measuring instruments were also used: questionnaire or survey in 24 studies (unique instrument in 23 [ 25 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ,…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies’ results ( n = 25) found a relation between parent’s PA or sport participation and children’s PA level or sport participation [ 25 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 65 , 68 , 69 , 70 , 71 ]. Four studies [ 51 , 53 , 64 , 67 ] did not find this relation and the other three [ 55 , 63 , 66 ] found relations between PA related features (dog walking and PA, parent’s PA and children’s BMI or body fat, and evidence of short co-participation parent/children PA time).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keluarga dengan orang tua dan anak-anak yang tinggal bersama sangat mendukung proses ini, sedangkan anak-anak yang dibesarkan dalam keluarga yang tidak utuh mengalami masalah dalam pencapaian prestasi, kognisi, emosi, dan perilaku (Steinbach dan Augustijn, 2022;Wang et al, 2022;. Keluarga merupakan faktor penting yang memengaruhi partisipasi anak dalam kegiatan fisik (Donnelly et al, 2022;Han dan Zheng, 2016;Mulhall et al, 2011). Selain itu, struktur keluarga berdampak pada anak (Ha et al, 2022;Wang et al, 2016).…”
Section: Pendahuluanunclassified
“…A family with parents and children living together best supports this process, whereas children raised in non-intact families lag in terms of their academic achievement (AA), cognition, emotions, and health behaviors (Steinbach and Augustijn, 2022;. Family is considered to be an important factor affecting children's participation in physical exercise (PE), with previous research demonstrating that the PE levels of children and parents are positively correlated (Donnelly et al, 2022;Han and Zheng, 2016;Mulhall et al, 2011). Moreover, family structure has a direct impact on PE behaviors, which are transmitted by parents to children; parents who regularly participate in PE play an obvious demonstrating and guiding role (Ha et al, 2022;.…”
Section: Introductionmentioning
confidence: 99%